2014
DOI: 10.3748/wjg.v20.i22.7040
|View full text |Cite
|
Sign up to set email alerts
|

Placement of prophylactic pancreatic stents to prevent post-endoscopic retrograde cholangiopancreatography pancreatitis in high-risk patients: A meta-analysis

Abstract: Placement of prophylactic pancreatic stents may lower the incidence of post-ERCP pancreatitis in high-risk patients and alleviate the severity of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 30 publications
0
34
0
1
Order By: Relevance
“…The reason for this result may be due to the fact that pancreatic stents may have been inserted in patients with higher risk of PEP because this study is not a randomized controlled study. Regardless of this reason, we should keep in mind that pancreatic stents cannot completely prevent PEP in SOD, but they may reduce the disease severity . In the present study, the severity of pancreatitis in six patients with pancreatic stent placement was mild to moderate and severe pancreatitis occurred in a patient without pancreatic stent.…”
Section: Discussionmentioning
confidence: 52%
“…The reason for this result may be due to the fact that pancreatic stents may have been inserted in patients with higher risk of PEP because this study is not a randomized controlled study. Regardless of this reason, we should keep in mind that pancreatic stents cannot completely prevent PEP in SOD, but they may reduce the disease severity . In the present study, the severity of pancreatitis in six patients with pancreatic stent placement was mild to moderate and severe pancreatitis occurred in a patient without pancreatic stent.…”
Section: Discussionmentioning
confidence: 52%
“…Pancreatic duct stents and/or postprocedure rectal nonsteroidal anti-inflammatory drug suppositories should be utilized to lower the risk of severe post-ERCP pancreatitis (PEP) in high-risk patients [8] . Some meta-analyses report that placement of prophylactic pancreatic stents may lower the overall incidence of PEP in high-risk patients, but not the incidence of severe PEP [9] . Furthermore, some debate still exists regarding the use of indomethacin [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of prospective trials have suggested benefit from PPS. [98][99][100][101] The number needed to treat to prevent one case of PEP is less than 10. More importantly, the risk of severe PEP is virtually abolished with PPS.…”
Section: Post-ercp Prophylaxismentioning
confidence: 99%
“…Finally and most concerning, about 5%-20% of attempted PPS fails and there can be substantial risk of PEP (35%-67%) associated with failed stent placement. 101,[111][112][113][114] From a meta-analysis, the risk of PEP after failed PPS placement was 19%. 101 Attempted but failed PPS stent placement is considered to have worse consequences in highrisk patients when compared to those not treated with pancreatic stents.…”
Section: Post-ercp Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation